Aryl-hydrocarbon receptor binding and the incidence of type 2 diabetes: the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - Bruce B. Duncan; Cristina D. Castilhos; Paula A. Bracco; Maria I. Schmidt; Sora Kang; Suyeol Im; Hong-Kyu Lee; Álvaro Vigo; Youngmi K. Pak (BMC, 2020)
Abstract Background Persistent organic pollutants (POPs) may cause diabetes, in part through aryl hydrocarbon receptor (AhR) binding. Ensuing mitochondrial dysfunction is postulated to mediate this effect. We aim to investigate the association of POPs with incident diabetes indirectly by bio-assaying AhR ligand bioactivity and intracellular ATP level induced by participant serum samples. Methods In incident case-cohort analyses of one ELSA-Brasil center, 1605 eligible subjects without diabetes at baseline had incident diabetes ascertained by self-report, medication use, OGTT or HbA1c at follow-up 4 years later. We assayed AhR ligand bioactivity (AhRL) and intracellular ATP content, the latter reflecting the presence of mitochondria-inhibiting substances (MIS), following incubation of recombinant mouse Hepa1c1c7 cells with participant sera for 71 incident diabetes cases and 472 randomly selected controls. Results In multiply-adjusted proportional hazards regression analyses, those with above-median AhRL and below-median MIS-ATP had 69 and 226% greater risk of developing diabetes (HR = 1.69; 95%CI 1.01-2.83 and 3.26; 1.84-5.78), respectively. A strong interaction was seen between the two exposures (HRhigh AhRL/low MIS-ATP vs. low AhRL/high MIS-ATP = 8.15; 2.86-23.2). Conclusion The markedly increased incidence of diabetes seen in those with both higher AhR ligand bioactivity and increased mitochondrial inhibition supports the hypothesis that widespread POPs exposure contributes to the diabetes epidemic.